Cardigan Makrame Dengan Hiasan Bada Mudiak - Ramadhani, Sylvi Chyntia; Akbar, Taufik; Yulimarni, Yulimarni; Hendratno, Hendratno (SPACEPRO: Product Design Jurnal, 2023)
Bada Mudiak is a Minangkabau pattern inspired by fish. Bada Mudiak means small fish facing upstream. This pattern contains the meaning of life that is harmonious, compact, one-sided, harmonious, one-way, and purposeful. The concept of the work created is the application of Bada Mudiak to macrame cardigan created in the size and placement of Bada Mudiak pattern. The method used is called Gustami SP's three-stage theory, started from exploring the process of searching or exploring to make direct observations to find out Bada Mudiak's pattern as well as looking for reference sources and images through literature study. Designing starts from sketching, designing and continuing with the embodiment process by preparing the materials and tools used. The work was created using 2 mm black, yellow, and red cotton rope. Macrame technique is used to create cardigans, and embroidery techniques is used to combine Bada Mudiak pattern on it.Each work created has a different meaning and title, namely: Ka Hulu, Indak Saliang Manyalo, Bairingan, Basamo Balapang-Lapang, Cilako Jikok Basilang, Saraso, and Tongga Babeleng. Keywords: Bada Mudiak, Cardigan, Macrame, Embroider